Mn/Cu nanoclusters-grafted N-doped carbon nanotubes: Robust oxygen electrode catalysts for Zn-air batteries. (16th October 2020) - Wang, Li; Cui, Lili; Ge, Xin; Yue, Nailin; He, Xingquan; Zhang, Wei; Asefa, Tewodros
Abstract: Developing efficient nonprecious electrocatalysts that can drive the oxygen electrode reactions in zinc-air batteries (ZABs) is important but remains challenging. In this work, novel materials comprising Mn/Cu nanoclusters-grafted N-doped carbon nanotubes are synthesized by preparing and then pyrolyzing Mn/Cu polyphthalocyanine-encapsulated carbon nanotubes (CNTs), followed by treating the products with acidic solution. The materials are named CNTs@(Mn, Cu)PPc-T, where T denotes the pyrolysis temperature in °C, and they are demonstrated to serve as efficient oxygen electrode catalysts for zinc-air batteries (ZABs). Among them, the one synthesized at 900 °C, CNTs@(Mn, Cu)PPc-900, requires more positive onset and half-wave potentials for reduction of oxygen and a low overpotential for the evolution of oxygen. A rechargeable ZAB assembled with CNTs@(Mn, Cu)PPc-900 electrocatalyst delivers a high power density (158.5 mW cm −2 ) and displays an excellent stability in 200 cycles of charge/discharge (in over 33 h). Such performance is even superior to that of a ZAB containing the benchmark Pt/C + RuO2 catalyst as an air cathode under identical testing condition. Graphical abstract: Hybrid materials composed of dual-metal Mn/Cu nanoclusters and N-doped carbon nanotubes are synthesized by pyrolyzing Mn/Cu-polyphthalocyanine-coated carboxylic acid-functionalized carbon nanotubes and then treating the carbonized product with acidic solution. The material synthesized under an optimal condition shows an excellent dual-function electrocatalytic activity for ORR and OER and a good performance as an electrocatalyst in a rechargeable Zn-air battery. Image 1 Highlights: Mn/Cu clusters-grafted N-doped carbon coated carbon nanotubes (CNTs) are reported. The materials are derived from Mn, Cu-polyphthalocyanine-encapsulated CNTs. The materials are synthesized through pyrolysis and acid etching synthetic steps. The optimized material shows excellent catalytic activity for both ORR and OER. The home-made Zn-air battery achieves a high peak power density (158.5 mW cm −2 ).